Spaces and Identities in Border Regions Politics - Media - Subjects - Wille, Christian; Reckinger, Rachel; Kmec, Sonja; Hesse, Markus (Kultur und soziale Praxis, 2015)
Spatial and identity research operates with differentiations and relations. These are particularly useful heuristic tools when examining border regions where social and geopolitical demarcations diverge. Applying this approach, the authors of this volume investigate spatial and identity constructions in cross-border contexts as they appear in everyday, institutional and media practices. The results are discussed with a keen eye for obliquely aligned spaces and identities and relinked to governmental issues of normalization and subjectivation. The studies base upon empirical surveys conducted in Germany, France, Belgium and Luxembourg.